Inequalities in child immunization coverage: potential lessons from the Guinea-Bissau case - Beatriz Raffi Lerm; Yanick Silva; Bianca O. Cata-Preta; Camila Giugliani (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Immunization is one of the main interventions responsible for the decline in under-5 mortality. This study aimed to assess full immunization coverage trends and related inequalities, according to wealth, area of residence, subnational regions, and maternal schooling level in Guinea-Bissau. Data from the 2006, 2014, and 2018 Guinea-Bissau Multiple Indicator Cluster Surveys (MICS) were analyzed. The slope index of inequality (SII) was estimated by logistic regression for wealth quintiles and maternal schooling level as a measure of absolute inequality. A linear regression model with variance-weighted least squares was used to estimate the annual change of immunization indicators at the national level and for the extremes of wealth, maternal schooling level, and urban-rural areas. Full immunization coverage increased by 1.8p.p./year (95%CI: 1.3; 2.3) over the studied period. Poorer children and children born to uneducated mothers were the most disadvantaged groups. Over the years, wealth inequality decreased and urban-rural inequalities were practically extinguished. In contrast, inequality of maternal schooling level remained unchanged, thus, the highest immunization coverage was among children born to the most educated women. This study shows persistent low immunization coverage and related inequalities in Guinea-Bissau, especially according to maternal schooling level. These findings reinforce the need to adopt equity as a main principle in the development of public health policies to appropriately reduce gaps in immunization and truly leave no one behind in Guinea-Bissau and beyond.